Fluid metabolic pathways after subarachnoid hemorrhage. Issue 1 (12th July 2021) - Zhou, Jiru; Guo, Peiwen; Guo, Zongduo; Sun, Xiaochuan; Chen, Yujie; Feng, Hua
Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating cerebrovascular disease with high mortality and morbidity. In recent years, a large number of studies have focused on the mechanism of early brain injury (EBI) and delayed cerebral ischemia (DCI), including vasospasm, neurotoxicity of hematoma and neuroinflammatory storm, after aSAH. Despite considerable efforts, no novel drugs have significantly improved the prognosis of patients in phase III clinical trials, indicating the need to further re‐examine the multifactorial pathophysiological process that occurs after aSAH. The complex pathogenesis is reflected by the destruction of the dynamic balance of the energy metabolism in the nervous system after aSAH, which prevents the maintenance of normal neural function. This review focuses on the fluid metabolic pathways of the central nervous system (CNS), starting with ruptured aneurysms, and discusses the dysfunction of blood circulation, cerebrospinal fluid (CSF) circulation and the glymphatic system during disease progression. It also proposes a hypothesis on the metabolic disorder mechanism and potential therapeutic targets for aSAH patients. Cover Image for this issue:  https://doi.org/10.1111/jnc.15384 . Abstract : Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating cerebrovascular disease with high mortality and morbidity. Aneurysm rupture causes high‐pressure blood to rush into the subarachnoid space and the nearby cistern, resulting in an increase of intracranial pressure and a sharp decrease of cerebral blood flow. The aversive effects of hematoma and toxic metabolites interrupt the microcirculation. Multiple factors act toward obstruction of the cerebrospinal fluid (CSF) circulation and absorption disturbance. The ability of the glymphatic system to drive interstitial fluid is impaired, limiting the excretion efficiency of toxic metabolites in the brain. This review article focuses on the fluid metabolic pathways of the central nervous system (CNS), starting with ruptured aneurysms, and discusses the dysfunction of blood circulation, CSF circulation, and the glymphatic system during aSAH progression. We also propose a hypothesis on the mechanism behind the metabolic disorder, and discuss potential therapeutic targets for aSAH.